The Impact of the Financial Crisis on Poverty and Income Distribution : Insights from Simulations in Selected Countries - Habib, Bilal; Narayan, Ambar; Olivieri, Sergio; Sanchez, Carolina (World Bank, Washington, DC, 2012)
As the financial crisis has spread through the world, the lack of real-time data has made it difficult to track its impact in developing countries. The authors use a micro-simulation approach to assess the poverty and distributional effects of the crisis. In Bangladesh, Mexico, and the Philippines, the authors find increases in both the level and the depth of aggregate poverty. Income shocks are relatively large in the middle (and, in Mexico, the bottom) parts of the income distribution. The authors also find that characteristics of people who become poor because of the crisis are different from those of both chronically poor people and the general population. Findings will be useful for policy makers wishing to identify leading monitoring indicators to track the impact of macroeconomic shocks and to design policies that protect vulnerable groups.